GENDING SORAN DALAM KARAWITAN GAYA YOGYAKARTA - Sugimin Sugimin (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2006)
Gending Soran is a Javanese piece performed with accent certain instruments, such as balungan, bonang, and drum. The way to play those instruments is by hitting strongly, and it impacts a loud sound (Javanese: sora). By Javanese ic society, the piece which is performed loudly, is called gending soran. The existence of gending soran injogyanese karawitan is very much influenced by psychological factors of the authoritative people during the Sultan Hamengku Buana I, who wonted to express the military spirit into the way of playing witan. Gending soran is pretended to have the feeling of heaviness which contains expression of seriousness and the noble of the Sultan Hamengku Buana I.Keywords:Â gending soran, military spirit, expression of seriousness.